Remedial measures for financial crisis in the light of prophetic teachings / Irfan Shahid. - Shahid, Irfan (Universiti Teknologi Mara Selangor, 2015)
A few years ago the world suffered from a financial turmoil which emerged in the United States of America, Europe and Asia. It made a large population redundant; many businesses shuttered down and reduced consumption, production, purchasing power, GDP and leading many economies into deep recession. Consequently poor and middle class people found difficult to survive. In the beginning of the financial crisis many suggestions were propounded by economists, policy makers and bankers to reduce its impact. Several policies were implemented to combat against financial crisis yet billion of people are suffering from poverty and hunger. Prophetic teaching is a complete code of life; in its guidance there is a set of teachings which govern financial issues of the society and the market. This paper aims to explore the measure suggested in the light of the Hadith and the Quran